A Polarographic Study of Cd(II) and Pb(II)-Imidazole-Sulphosalicylate Mixed Ligand Complexes - Paliwal, R.K. (Asian Journal of Chemistry, 2010)
The stability constant of mixed ligand complexes of imidazole and sulphosalicylate with Cd(II) and Pb(II) were determined polarographically. The values of stability constants of these soluble mixed ligand complexes [Cd(Im) (SSA)], [Cd(Im) (SSA)2]2-, [Cd(Im)2 (SSA)] and [Pb(SSA) (Im)] are found to be log β11 = 4.19, log β12 = 3.70, log β21 = 4.38 and log β11 = 4.08, respectively at pH = 7.4 and 25 ± 0.1 ºC.